Anode and method for manufacturing the same, and, non-aqueous electrolyte secondary battery including anode and method for manufacturing the same
By forming a connecting layer composed of PAA and SBR in the negative electrode of the nonaqueous electrolyte secondary battery, the problem of reducing electron conductivity caused by expansion and contraction of the negative electrode material during charging and discharging is solved, and the cycling performance of the battery is improved.
Patent Information
- Application Number
- JP2023145314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2043-09-07
AI Technical Summary
The expansion and contraction of the negative electrode materials of the existing nonaqueous electrolyte secondary battery during charging and discharging lead to a decrease in the conductivity of the electronics, affecting the cycling performance of the battery.
Using a negative electrode containing a carbon-based active material and a metal-based active material, a connecting layer consisting of polypropylene (PAA) and styrene butadiene rubber (SBR) is formed in the active material layer. The connecting layer comes into contact with the surface of the active material particles through the first layer and the second layer, respectively, forming a stable connecting structure.
By forming a stable connecting layer, the expansion and contraction of the active material during charging and discharging is effectively suppressed, the electronic conductivity is maintained, and the circulation performance of the battery is improved.
Smart Images

Figure 2025038597000002 
Figure 2025038597000003 
Figure 2025038597000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a method for producing the same, and to a non-aqueous electrolyte secondary battery including the negative electrode and a method for producing the same. [Background technology]
[0002] In order to increase the capacity of the negative electrode of a non-aqueous electrolyte secondary battery, it is known to use, together with graphite, an Si-based active material such as SiOx, which can achieve a higher capacity than graphite (Patent Documents 1 and 2, etc.). Compared with graphite, Si-based active materials expand and contract more greatly during charging and discharging of a secondary battery, which causes a decrease in electronic conductivity in the active material layer and tends to reduce the capacity retention rate after charge-discharge cycles.
[0003] Patent Document 1 discloses that the use of polyacrylic acid suppresses expansion and contraction of a secondary battery during charging and discharging. Patent Document 2 discloses that the formation of a coating layer of polyacrylic acid on a carbon-based active material and a Si-based active material and optimizing the content ratio of polyacrylic acid suppresses the swelling of the secondary battery and suppresses the decrease in discharge capacity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-53152 A [Patent Document 2] International Publication No. 2017 / 026268 Summary of the Invention [Problem to be solved by the invention]
[0005] Secondary batteries are required to have further improved cycle characteristics. The present disclosure has an object to provide a negative electrode that can provide a secondary battery having excellent cycle characteristics, a method for manufacturing the negative electrode, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for manufacturing the same. [Means for solving the problem]
[0006] [1] A negative electrode for a non-aqueous electrolyte secondary battery having an active material layer containing active material particles, the active material particles include carbon-based active material particles and metal-based active material particles, the active material layer has a connecting portion connecting two of the active material particles, the connecting portion has a first layer including at least one of polyacrylic acid and a salt thereof, and a second layer formed on a surface of the first layer and including styrene-butadiene rubber, the first layer and the second layer are both in contact with the surfaces of the two active material particles connected by the connecting portion. [2] The negative electrode according to [1], wherein the carbon-based active material particles include graphite particles. [3] The negative electrode according to [1] or [2], wherein the metal-based active material particles include one or more particles selected from the group consisting of Si, SiOx, and a composite of Si and C. [4] The negative electrode according to any one of [1] to [3], wherein the connecting portion connects at least the carbon-based active material particles and the metal-based active material particles. [5] The negative electrode according to any one of [1] to [4], wherein the active material layer further contains a conductive assistant. [6] The negative electrode according to any one of [1] to [5], wherein the active material layer further contains carboxymethyl cellulose. [7] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [6]. [8] A method for producing a negative electrode for a non-aqueous electrolyte secondary battery having an active material layer containing active material particles, comprising: A method for producing a kneaded body, a second step of producing a slurry using the kneaded body, and a third step of forming the active material layer using the slurry, The first step includes a step of kneading active material particles, polyacrylic acid hydrate obtained by hydrating at least one of polyacrylic acid and a salt thereof, and water, the active material particles include carbon-based active material particles and metal-based active material particles, The second step includes a step of adding styrene-butadiene rubber and water to the kneaded body and kneading the mixture, When a mixture of the active material particles and the polyacrylic acid and its salt in the ratio contained in the kneaded body is added with water and kneaded, the solid content ratio at which the torque becomes maximum is defined as the ideal solid content ratio B0 [wt %]. The solid content of the kneaded body is (B0-5) to B0 [wt%], The method for producing a negative electrode, wherein the slurry has a solid content of (B0-25) to (B0-10) [wt %]. [9] The method for producing a negative electrode according to [8], wherein the kneading step in the first step is performed by further adding carboxymethyl cellulose.
[10] The method for producing a negative electrode according to [8] or [9], wherein the kneading step in the first step is carried out by further adding a conductive assistant.
[11] The method for producing a negative electrode according to any one of [8] to
[10] , wherein the carbon-based active material particles include graphite particles.
[12] The method for producing a negative electrode according to any one of [8] to
[11] , wherein the metal-based active material particles contain one or more types of particles selected from the group consisting of Si, SiOx, and a composite of Si and C.
[13] A method for producing a non-aqueous electrolyte secondary battery, comprising a step of producing a negative electrode by the method for producing a negative electrode according to any one of [8] to
[12] . Effect of the Invention
[0007] According to the negative electrode of the present disclosure, a nonaqueous electrolyte secondary battery having excellent cycle characteristics can be obtained. [Brief description of the drawings]
[0008] [Figure 1] 2 is a flowchart showing a method for manufacturing a negative electrode according to an embodiment. [Diagram 2] 2 is a scanning transmission electron microscope image of the active material layer obtained in Example 1. [Diagram 3] 1 is a scanning transmission electron microscope image of the active material layer obtained in Example 2. [Figure 4]1 is a scanning transmission electron microscope image of the active material layer obtained in Comparative Example 1. [Diagram 5] 1 is a scanning transmission electron microscope image of the active material layer obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, a numerical range such as "x to y" includes an upper limit and a lower limit unless otherwise specified. That is, "x to y" represents a numerical range of "not less than x and not more than y". A numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, or in a figure, etc.
[0010] (Negative electrode) The negative electrode of this embodiment (hereinafter also referred to as "the present negative electrode") is a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery"), and has an active material layer containing active material particles. The active material particles include carbon-based active material particles (hereinafter also referred to as "carbon-based particles") and metal-based active material particles (hereinafter also referred to as "metal-based particles"). The active material layer has a connecting portion connecting two active material particles. The connecting portion has a first layer containing at least one of polyacrylic acid and a salt thereof (hereinafter also referred to as "PAA"), and a second layer formed on the surface of the first layer and containing styrene butadiene rubber (hereinafter also referred to as "SBR"). Both the first layer and the second layer are in contact with the surfaces of the two active material particles connected by the connecting portion.
[0011] The carbon-based particles, which are active material particles, preferably contain one or more types of particles selected from the group consisting of carbon (C) such as graphite, hard carbon, soft carbon, and amorphous coated graphite, or are one or more types of particles selected from the group, and preferably contain graphite particles or are graphite particles.
[0012] The metal-based particles, which are active material particles, include particles of metal elements such as metal simple substances or metal oxides containing elements selected from the group consisting of silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal-based particles are preferably one or more particles selected from the group consisting of Si, SiOx (x=0.5 to 1.5), a composite of Si and C (hereinafter also referred to as "SiC composite"), and Sn, and more preferably one or more particles selected from the group consisting of Si, SiOx, and SiC composite. The metal-based particles are more preferably SiC composite particles. The SiC composite is, for example, a composite in which Si is dispersed in a carbon matrix.
[0013] The average particle diameter D50 of the metal-based particles is, for example, 3 to 15 μm, and preferably 5 to 10 μm. In this specification, the average particle diameter D50 is the particle diameter at which the cumulative frequency from the smallest particle diameter in the volumetric particle size distribution is 50%. The volumetric particle size distribution can be measured by a laser diffraction particle size distribution measuring device.
[0014] The total content of the carbon-based particles and the metal-based particles contained in the active material particles may be 90 to 100% by weight, 90 to 99% by weight, or 92 to 95% by weight based on the total amount of the active material particles. The content ratio of the carbon-based particles to the metal-based particles in the active material particles (carbon-based particles:metal-based particles) (weight ratio) may be 70:30 to 95:5, 80:20 to 92:8, or 85:15 to 95:5.
[0015] The negative electrode may have an active material layer on a negative electrode current collector. The active material layer may be formed on only one side of the negative electrode current collector, or on both sides. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy.
[0016] When active material layers are formed on both sides of the negative electrode current collector, the weight of the active material layers on each side (total of both sides) is, for example, 150 to 250 g / m 2and 170 to 230 g / m 2 and 180 to 220 g / m 2 The weight per surface of the negative electrode current collector may be, for example, half of the weight per surface of both surfaces described above. The thickness of the active material layer per surface may be, for example, 90 to 200 μm, 100 to 180 μm, or 110 to 150 μm. The packing density of the active material layer can be calculated by the following formula, and may be, for example, 1.3 to 1.9 g / cc, 1.4 to 1.8 g / cc, or 1.5 to 1.7 g / cc. Packing density [g / cc] = active material layer weight [g / m 2 ] / active material layer thickness [μm]
[0017] The active material layer has a connecting portion, and the connecting portion connects two active material particles in the active material layer. The active material layer has a connecting portion, which makes it easy to form a conductive path between the active material particles via a conductive material or the like. The connecting portion of the present negative electrode has a first layer and a second layer formed on the surface of the first layer. In the present negative electrode, since both the first layer and the second layer are in contact with the surface of the active material particle, the connecting portion can connect the active material particles by both the first layer and the second layer. The fact that the connecting portion has the first layer and the second layer can be confirmed by, for example, observing a spectral distribution using a scanning transmission electron microscope image (hereinafter also referred to as "SEM image") or an SEM-EDX (energy dispersive X-ray spectroscopy) spectrum.
[0018] The length of the connecting portion (the distance in the direction connecting two active material particles) may be 0.1 to 5 μm, 0.5 to 4 μm, or 1 to 3 μm. The diameter of the connecting portion may be 0.1 to 1 μm, 0.2 to 0.9 μm, or 0.3 to 0.8 μm. The length and diameter of the connecting portion can be determined by analysis of SEM images.
[0019] The first layer contains PAA. PAA may be in the form of an acid (polyacrylic acid) or a salt (polyacrylate), or may contain both, but preferably contains a salt. PAA is preferably in the form of a salt. Examples of the salt include alkali metal salts such as potassium and sodium. PAA has excellent binding properties, imparts mechanical strength (hardness) to the connection portion, and easily maintains the distance between two active material particles. As a result, even when the active material particles expand and contract due to charging and discharging of the secondary battery, the distance between the two active material particles can be kept small, making it easier to ensure the conductivity of the active material layer.
[0020] The second layer may be formed on the surface of the first layer, but is preferably formed so as to cover the entire surface of the first layer, and may cover the first layer so that the surface of the first layer is not exposed. The second layer contains SBR. Since SBR has excellent flexibility, it can form a connecting part that follows the expansion and contraction of the active material particles accompanying the charge and discharge of the secondary battery.
[0021] As described above, the connecting part has the first layer and the second layer, and the distance between the active material particles can be kept small, and the connecting part can be formed so that the connecting part is less likely to be cut even when the active material particles expand and contract due to the charge and discharge of the secondary battery, compared to a connecting part formed in a state where PAA and SBR are mixed. The connecting part can also connect two active material particles arranged at relatively distant positions in the active material layer. This makes it easier to form a conductive path via a conductive assistant or the like in the active material layer, making it easier to obtain a secondary battery with excellent cycle characteristics. The connecting part having the first layer and the second layer can be obtained, for example, by the manufacturing method of the negative electrode described later.
[0022] The two active material particles connected by the connecting portion may be two carbon-based particles, two metal-based particles, or a carbon-based particle and a metal-based particle. The metal-based particles expand and contract more when the secondary battery is charged and discharged than the carbon-based particles. It is considered that the connecting portion between the metal-based particle and another active material particle (between the carbon-based particle and the metal-based particle, or between two metal-based particles) is more likely to be cut when the secondary battery is charged and discharged than the connecting portion between two carbon-based particles. In the present negative electrode, the connecting portion has a first layer having excellent hardness and a second layer having excellent flexibility, so that the connecting portion can be given appropriate strength and flexibility. Therefore, even when at least one of the two active material particles connected by the connecting portion is a metal-based particle, the connecting portion can be prevented from being cut when the secondary battery is charged and discharged.
[0023] The content of PAA and SBR in the connecting portion is preferably 1:1.2 to 1:15 in terms of PAA:SBR (volume ratio), and may be 1:1.25 to 1:12, or may be 1:1.3 to 1:10. The content of PAA and SBR in the connecting portion can be determined by dyeing the PAA and SBR and observing the spectral distribution by SEM-EDX spectrum, as described in the Examples below.
[0024] At least one of PAA and SBR that does not form a connecting portion may be formed on the surface of the active material particle contained in the active material layer. It is preferable that the PAA and SBR on the surface of the active material particle that does not form a connecting portion does not have a first layer and a second layer like the connecting portion, and that the PAA and SBR are each independently arranged to cover the surface of the active material particle.
[0025] The active material layer may contain a conductive assistant. Examples of the conductive assistant include one or more carbon materials selected from the group consisting of fibrous carbon, carbon black (acetylene black, ketjen black, etc.), coke, and activated carbon. Examples of the fibrous carbon include carbon nanotubes (hereinafter also referred to as "CNT"). The CNT may be a single-walled carbon nanotube (SWCNT) or a multi-walled carbon nanotube such as a double-walled carbon tube (DWCNT). As described above, the connecting portion has a structure that is difficult to break and easily follows the expansion and contraction of the active material particles accompanying the charging and discharging of the secondary battery, and can also connect two active material particles arranged at relatively distant positions in the active material layer. The conductive assistant is arranged around the connecting portion, and can form a conductive path between the active material particles. Therefore, the connecting portion having the first and second layers and the conductive assistant present around this connecting portion make it easy to form a good conductive path that is difficult to break in the active material layer. This makes it possible to obtain a secondary battery with excellent cycle characteristics.
[0026] The active material layer may contain carboxymethyl cellulose (CMC). The CMC may be in the form of an acid or a salt, but is preferably in the form of a salt. By containing CMC, the connecting portion is easily formed uniformly in the active material layer.
[0027] The yield loop height measured by the stiffness test for this negative electrode is preferably 18 mm or less, may be 15 μm or less, may be 12 μm or less, may be 1 to 18 μm, may be 2 to 15 μm, or may be 2 to 12 μm. The yield loop height is the height of the loop when the stress of the stiffness curve measured by pressing the outer circumferential surface of a single-sided electrode plate having an active material layer formed only on one side of a negative electrode current collector is amplified by butting both ends of the single-sided electrode plate so that the outer circumferential surface is the active material layer, and the stress of the stiffness curve measured by pressing the outer circumferential surface of the loop shows an inflection point where the stress rises and then falls sharply. The yield loop height can be adjusted, for example, by the type of SBR contained in the active material layer.
[0028] (Method of manufacturing negative electrode) FIG. 1 is a flow chart showing a method for manufacturing a negative electrode according to an embodiment. The method for manufacturing a negative electrode according to the present embodiment can manufacture a negative electrode for a secondary battery, and can also manufacture the present negative electrode. The method for manufacturing a negative electrode includes a first step of obtaining a first kneaded body (kneaded body), a second step of obtaining a slurry using the first kneaded body, and a third step of forming an active material layer using the slurry (FIG. 1). The first step includes a step of kneading active material particles, polyacrylic acid hydrate (hereinafter also referred to as "PAA hydrate") obtained by hydrating PAA, and water. The active material particles include carbon-based particles and metal-based particles. Examples of the active material particles (carbon-based particles and metal-based particles) and PAA include the materials described above. The second step of the method for manufacturing a negative electrode includes a step of adding SBR and water to the first kneaded body and kneading the mixture.
[0029] When a mixture (mixed powder) of active material particles and PAA in the ratio contained in the first kneaded body is added with water and kneaded, the solid content at which the torque is maximum is taken as the ideal solid content B0 [weight %]. The solid content of the first kneaded body is (B0-5) to B0 [weight %], and the solid content of the slurry is (B0-25) to (B0-10) [weight %].
[0030] The ideal solid content B0 [wt%] can be calculated by the following formula, where A0 [wt%] is the moisture content at which the torque required for kneading is maximum when a mixture (mixed powder) of active material particles and PAA in the above ratio is added with water and kneaded, and A1 [mL] is the moisture content per 100 g of the above mixture (mixed powder) corresponding to the moisture content A0 [wt%]. The ideal solid content B0 [wt%] is, for example, 55 to 75%. B0 [weight %] = 100 - A0 = {100 / (100+A1)} x 100
[0031] The solid content of the first kneaded body is (B0-5) to B0 [wt %], may be (B0-4) to B0 [wt %], may be (B0-3) to B0 [wt %], or may be (B0-2) [wt %] or more and less than B0 [wt %]. The solid content of the first kneaded body is calculated as the weight ratio [wt %] of the solid content (components other than water) to the total weight of the first kneaded body. By performing kneading so as to obtain a first kneaded body having the above solid content range, the first layer of the connecting portion can be well formed between the active material particles.
[0032] The ratio of PAA to water contained in the PAA hydrate may be 1:1 to 1:100, 1:1 to 1:50, 1:2 to 1:20, 1:5 to 1:10, or 1:1 by weight. The method for producing a negative electrode may include a step of obtaining a PAA hydrate by mixing PAA with water and hydrating the PAA prior to the first step. The mixing ratio of PAA to water used in hydrating the PAA may be within the above-mentioned range of the PAA to water content contained in the PAA hydrate. By using the PAA hydrate in the first step, the thickness (width) of the first layer of the connection portion formed between the active material particles can be increased.
[0033] The kneading step in the first step may further include the addition of CMC. That is, in the first step, CMC may be added and kneaded together with the active material particles, PAA hydrate, and water. Examples of CMC include the above-mentioned materials. Since the first step is a kneading step, the active material particles and PAA hydrate tend to aggregate. By adding CMC in the first step, the aggregation of the active material particles and PAA hydrate can be suppressed, and the active material particles and PAA can be well dispersed. This allows the first layer of the connection portion to be uniformly formed between the active material particles in the active material layer.
[0034] When CMC is added and kneaded in the first step, the method for producing a negative electrode may include a step of dry-mixing the active material particles and CMC to obtain a mixed powder prior to the first step. In this case, the first step may obtain a first kneaded body by kneading the mixed powder, PAA hydrate, and water.
[0035] The kneading step in the first step may further include the addition of a conductive assistant. That is, in the first step, the conductive assistant may be added together with the active material particles, the PAA hydrate, and the water, and then kneaded. Examples of the conductive material include the above-mentioned materials. When CMC and the conductive assistant are added and kneaded in the first step, the mixed powder, the PAA hydrate, the conductive assistant, and the water may be kneaded in the first step. By kneading the conductive assistant in the first step, the conductive assistant can be arranged around the connecting parts, and therefore a good conductive path can be formed in the active material layer.
[0036] The first step may be carried out using a stirrer having a stirring blade. The rotation speed of the stirring blade in the first step is not particularly limited, but may be, for example, 40 to 70 rpm, 45 to 65 rpm, or 50 to 55 rpm. The kneading time in the first step may be, for example, 100 to 200 min, 20 to 120 min, or 30 to 100 min.
[0037] The second step is performed to adjust the solid content concentration of the slurry. The solid content rate of the slurry is (B0-25) to (B0-10) [weight %], or may be (B0-22) to (B0-11) [weight %], or may be (B0-18) to (B0-12) [weight %], or may be (B0-16) to (B0-11) [weight %]. The solid content rate of the slurry is calculated as the weight ratio [weight %] of the solid content (components other than water) to the total weight of the slurry.
[0038] The SBR added in the second step may be added as an aqueous SBR solution. The second step may include a step (2.1) of kneading the first kneaded body with water to obtain a second kneaded body, and a step (2.2) of mixing the second kneaded body with SBR (aqueous SBR solution). In the second step, since SBR and water are added to the first kneaded body, a second layer containing SBR can be formed on the surface of the first layer formed between the active material particles.
[0039] The second step may be carried out using a stirrer having a stirring blade. The rotation speed of the stirring blade in the second step is not particularly limited, and may be, for example, 10 to 40 rpm, 20 to 35 rpm, or 25 to 30 rpm. The stirring time in the second step may be, for example, 10 to 90 min, 15 to 60 min, or 20 to 50 min. The kneading time in step (2.1) may be, for example, 15 to 45 min, or 20 to 40 min. The mixing time in step (2.2) may be, for example, 1 to 20 min, or 5 to 15 min. The kneading time in step (2.1) may be longer than the mixing time in step (2.2).
[0040] The third step is a step of forming an active material layer using the slurry prepared in the second step. The second step may include a step of applying the slurry onto a negative electrode current collector to form a coating layer, drying the coating layer, and may further include a step of compressing the coating layer after drying. The negative electrode current collector may be made of the above-mentioned materials.
[0041] (Nonaqueous electrolyte secondary battery) The nonaqueous electrolyte secondary battery of this embodiment (hereinafter also referred to as "the battery") includes the present negative electrode, and typically includes an electrode assembly including the present negative electrode, and a nonaqueous electrolyte. The battery may have a battery case that houses the electrode assembly and the nonaqueous electrolyte. The battery case may include an exterior body having an opening, and a sealing plate that seals the opening. The exterior body and the sealing plate are preferably made of metal, and may be formed using aluminum, an aluminum alloy, iron, an iron alloy, or the like, and may be formed using, for example, an aluminum laminate film. A resin sheet serving as an electrode holder may be disposed between the electrode body and the exterior body.
[0042] The electrode body may include the present negative electrode, a positive electrode, and a separator. In the electrode body, the active material layer of the present negative electrode and the positive electrode active material layer of the positive electrode face each other via the separator. The electrode body may be a laminated type in which the present negative electrode, the positive electrode, and the separator are laminated, or a wound type in which a laminate in which the present negative electrode, the positive electrode, and the separator are laminated is wound.
[0043] The positive electrode usually has a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is, for example, a metal foil made of an aluminum material such as aluminum or an aluminum alloy. The positive electrode active material layer contains positive electrode active material particles, and may further contain a conductive material, a binder, and the like. The positive electrode active material particles include, for example, layered or spinel-based lithium transition metal oxides (e.g., LiNiCoMnO2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiCrMnO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the conductive material include carbon materials such as fibrous carbon (CNT (SWCNT, DWCNT)), carbon black (e.g., acetylene black, ketjen black), coke, and activated carbon. Examples of the binder include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and SBR.
[0044] The separator may have a substrate and a functional layer on at least one side of the substrate. The substrate may be a film made of a resin such as polyethylene, polypropylene, polyester, cellulose, polyamide, or the like, or a porous sheet such as a nonwoven fabric. The substrate may have a single-layer structure or a multi-layer structure. Examples of the functional layer include an adhesive layer and a heat-resistant layer, and the separator may have one or both of these. The adhesive layer may be formed, for example, by an adhesive. The heat-resistant layer may include, for example, a filler and a binder.
[0045] The non-aqueous electrolyte is preferably a non-aqueous solvent such as an organic solvent containing a supporting salt. Examples of the supporting salt include LiPF6, LiBF4, LiClO4, LiFSO3, and LiBOB (lithium bis(oxalato)borate). The non-aqueous electrolyte may contain one or more of these supporting salts. Examples of the non-aqueous solvent include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butylene carbonate (BC), and diethyl carbonate (DEC). The non-aqueous electrolyte may contain one or more of these non-aqueous solvents.
[0046] (Method of manufacturing non-aqueous electrolyte secondary battery) The method for producing the present battery includes a step of producing a negative electrode by the method for producing a negative electrode of the present invention. The method for producing the present battery may further include a step of obtaining an electrode assembly using the present negative electrode, a positive electrode, and a separator, and a step of housing the electrode assembly and a nonaqueous electrolyte in a battery case. EXAMPLES
[0047] The present disclosure will be described more specifically below with reference to examples and comparative examples. Example 1 (Preparation of negative electrode) Graphite particles were used as the carbon particles, and Si and C composite particles (SiC composite particles) were used as the metal particles. SWCNT was used as the conductive material. Slurry (1) was prepared using a mixer (PRIMIX Hivismix 2P-1 type) according to the following procedure.
[0048] First, PAA powder and water were mixed at a PAA powder:water = 1:1 (weight ratio) to obtain PAA hydrate. Carbon-based particles, metal-based particles, and CMC were dry-mixed to obtain mixed powder (1). PAA hydrate, mixed powder (1), SWCNT, and water were kneaded for 90 minutes at a solid content rate of 65% by weight with a stirrer rotation speed of 50 rpm to obtain a first kneaded body (first step). Next, the first kneaded body and water were kneaded for 30 minutes at a stirrer rotation speed of 30 rpm to obtain a second kneaded body, and an SBR aqueous solution was added to this second kneaded body and mixed for 10 minutes at a solid content rate of 50% by weight with a stirrer rotation speed of 30 rpm to obtain a slurry (1) with a solid content rate of 50% by weight (second step). The compounding ratio of the slurry (1) was graphite particles:SiC composite particles:SWCNT:CMC:PAA:SBR=90:10:0.05:1:1:1 (weight ratio).
[0049] When a mixture of graphite particles, SiC composite particles, and PAA in the ratios contained in the first kneaded body is added with water and kneaded, the moisture content at which the torque required for kneading is maximized is defined as A0 [wt %], and the moisture amount per 100 g of the mixture (mixed powder) corresponding to the moisture content A0 [wt %] is defined as A1 [mL], then the following formula: B0 [weight %] = 100 - A0 = {100 / (100+A1)} x 100 was 65% by weight. Therefore, in this example, the solid content of the first step was (B0-2) [% by weight], and the solid content of the slurry (1) was (B0-15) [% by weight].
[0050] The slurry (1) obtained above was applied to both sides of a copper foil having a thickness of 8 μm as a negative electrode current collector, dried, and compressed to obtain a negative electrode (1). The active material layer of the negative electrode (1) had a basis weight (total basis weight of both sides) of 215 g / m 2The thickness (per side) of the active material layer was 135 μm, and the packing density of the active material layer was 1.60 g / cc. As shown in FIG. 2, in the active material layer of the negative electrode (1), a thick columnar connection part having a first layer and a second layer formed on the surface of the first layer was formed between two active material particles, and both ends of the first layer and the second layer were in contact with the surface of the active material particle. FIG. 2 shows the connection part formed between the graphite particle and the SiC composite particle, but similar connection parts were also formed between the graphite particles and between the SiC composite particles.
[0051] (Preparation of positive electrode) The positive electrode active material particles were lithium nickel cobalt manganese composite oxide (NCM), the conductive material was acetylene black (AB), and the binder was polyvinylidene fluoride (PVdF) in a ratio of positive electrode active material particles:AB:PVdF=100:1:1 (weight ratio), which was mixed with N-methylpyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum foil with a thickness of 15 μm as a positive electrode current collector, dried, and compressed to obtain a positive electrode.
[0052] (Preparation of non-aqueous electrolyte secondary battery) Leads were attached to the negative and positive electrodes obtained above, and the negative and positive electrodes were laminated with a separator between them to obtain an electrode body. The electrode body was inserted into an exterior body made of an aluminum laminate sheet, a non-aqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell (laminated cell) (1). The non-aqueous electrolyte was a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=30:30:40, in which LiPF6 was dissolved as a lithium salt at a concentration of 1 mol / L.
[0053] Example 2 A slurry (2) was prepared in the same manner as in Example 1, except that the type of SBR contained in the SBR aqueous solution was changed, and a negative electrode (2) and a test cell (2) were obtained. The SBR used in this example was harder and less likely to be crushed than that used in Example 1. As shown in FIG. 3, in the active material layer of the negative electrode (2), a thick columnar connection part having a first layer and a second layer formed on the surface of the first layer was formed between two active material particles, and both ends of the first layer and the second layer were in contact with the surface of the active material particle. FIG. 3 shows the connection part formed between the graphite particles, but similar connection parts were also formed between the SiC composite particles and between the graphite particles and the SiC composite particles.
[0054] Comparative Example 1 (Preparation of negative electrode) A slurry (c1) was prepared by the following procedure to obtain a negative electrode (c1). In this comparative example, the same carbon-based particles, metal-based particles, PAA powder, SWCNT, SBR, and stirrer as those used in the preparation of the negative electrode in Example 1 were used.
[0055] First, carbon-based particles, metal-based particles, PAA powder, and CMC were dry-mixed to obtain a mixed powder (c1). The mixed powder (c1), SWCNT, SBR aqueous solution, and water were kneaded at a solid content rate of 65% by weight to obtain a kneaded body. Then, the kneaded body and water were kneaded to obtain a slurry (c1) with a solid content rate of 50% by weight. The mixing ratio of each component was the same as in Example 1. A negative electrode (c1) was obtained by the procedure for producing a negative electrode in Example 1, except that the slurry (c1) was used instead of the slurry (1). As shown in FIG. 4, in the active material layer of the negative electrode (c1), a thin columnar connection part with a single-layer structure formed of a mixture of PAA and SBR was formed between two active material particles. FIG. 4 shows the connection part formed between graphite particles, but the connection parts formed between SiC composite particles and between the graphite particles and the SiC composite particles were also thin columnar with a single-layer structure.
[0056] (Preparation of non-aqueous electrolyte secondary battery) A test cell (c1) was obtained in the same manner as in the preparation of the nonaqueous electrolyte secondary battery of Example 1, except that the negative electrode (c1) was used instead of the negative electrode (1).
[0057] Comparative Example 2 (Preparation of negative electrode) A slurry (c2) was prepared by the following procedure to obtain a negative electrode (c2). In this comparative example, the same carbon-based particles, metal-based particles, PAA powder, SWCNT, SBR, and agitator as those used in the preparation of the negative electrode in Example 1 were used.
[0058] First, carbon-based particles, metal-based particles, PAA powder, and CMC were dry-mixed to obtain a mixed powder (c2). The mixed powder (c2), SWCNT, SBR aqueous solution, and water were kneaded at a solid content rate of 50% by weight to obtain a slurry (c2) with a solid content rate of 50% by weight. The mixing ratio of each component was the same as in Example 1. A negative electrode (c2) was obtained by the procedure for producing a negative electrode in Example 1, except that the slurry (c2) was used instead of the slurry (1). As shown in FIG. 5, the structure formed between two active material particles in the active material layer of the negative electrode (c2) was a partially cut column structure or a very thin column structure, and was a single-layer structure. FIG. 5 shows the structure formed between the graphite particles, but the structures formed between the SiC composite particles and between the graphite particles and the SiC composite particles also had the same structure.
[0059] (Preparation of non-aqueous electrolyte secondary battery) A test cell (c2) was obtained in the same manner as in the preparation of the nonaqueous electrolyte secondary battery of Example 1, except that the negative electrode (c2) was used instead of the negative electrode (1).
[0060] [Measuring joints] (PAA and SBR content) The contents of PAA and SBR contained in the connecting portion were measured by the following procedure. The binder components were visualized by staining PAA with osmium (Os) and SBR with ruthenium (Ru) by a staining method. The spectral distribution was then observed by SEM-EDX spectrum to determine the contents (volume ratio) of PAA and SBR contained in the connecting portion. The results are shown in Table 1.
[0061] (length and diameter) The length and diameter of the junctions were measured for the junctions in the SEM images, and the average values were taken as the length and diameter of the junctions.
[0062] [Evaluation of cycle characteristics] In an environment of 25°C, the test cell was repeatedly charged to 4.15V and 0.1C by constant current / constant voltage charging (CCCV) at a current value of 0.2C, and then discharged to 3V at a current value of 0.33C (CC discharge), with this being one charge / discharge cycle. The cycle retention rate [%] was calculated as the discharge capacity at the 200th cycle relative to the discharge capacity at the 1st cycle according to the following formula. The results are shown in Table 1. Cycle retention rate [%] = (200th cycle discharge capacity / 1st cycle discharge capacity) x 100
[0063] [Stiffness test] The active material layer on one side of the negative electrode was peeled off, and the single-sided electrode plate with the active material layer formed only on one side of the negative electrode current collector was cut into a size of 10 mm wide x 80 mm long. The cut-out single-sided electrode plate was butted at both ends in the length direction so that the outer peripheral surface of the plate would be the active material layer, and rolled into a perfect circle in a single layer to prepare a measurement sample with an outer circumference of 80 mm. The butted portion of the measurement sample was fixed to the lower plate of the loop stiffness tester, and the measurement sample was sandwiched between the upper and lower plates. The outer peripheral surface of the measurement sample was pressed to measure the stiffness curve (stress generated in the measurement sample), and the inflection point where the stiffness curve rose and then suddenly dropped was determined, and the distance between the upper and lower plates at this inflection point was measured as the height of the yield loop. The results are shown in Table 1.
[0064] [Table 1]
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery having an active material layer containing active material particles, the active material particles include carbon-based active material particles and metal-based active material particles, the active material layer has a connecting portion connecting two of the active material particles, the connecting portion has a first layer including at least one of polyacrylic acid and a salt thereof, and a second layer formed on a surface of the first layer and including styrene-butadiene rubber, the first layer and the second layer are both in contact with surfaces of the two active material particles connected by the connecting portion.
2. The negative electrode according to claim 1 , wherein the carbon-based active material particles include graphite particles.
3. 2. The negative electrode according to claim 1, wherein the metal-based active material particles include particles of one or more types selected from the group consisting of Si, SiOx, and a composite of Si and C.
4. The negative electrode according to claim 1 , wherein the connecting portion connects at least the carbon-based active material particles and the metal-based active material particles.
5. The negative electrode according to claim 1 , wherein the active material layer further comprises a conductive assistant.
6. The negative electrode according to claim 1 , wherein the active material layer further comprises carboxymethyl cellulose.
7. A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of claims 1 to 6.
8. A method for producing a negative electrode for a non-aqueous electrolyte secondary battery having an active material layer containing active material particles, comprising: A method for producing a kneaded body, a second step of producing a slurry using the kneaded body, and a third step of forming the active material layer using the slurry, The first step includes a step of kneading active material particles, polyacrylic acid hydrate obtained by hydrating at least one of polyacrylic acid and a salt thereof, and water, the active material particles include carbon-based active material particles and metal-based active material particles, The second step includes a step of adding styrene-butadiene rubber and water to the kneaded body and kneading the mixture, When a mixture of the active material particles and the polyacrylic acid and its salt in the ratio contained in the kneaded body is added with water and kneaded, the solid content ratio at which the torque becomes maximum is defined as the ideal solid content ratio B0 [wt %]. The solid content of the kneaded body is (B0-5) to B0 [wt%], The method for producing a negative electrode, wherein the slurry has a solid content of (B0-25) to (B0-10) [wt %].
9. The method for producing a negative electrode according to claim 8 , wherein the kneading step in the first step is performed by further adding carboxymethyl cellulose.
10. The method for producing a negative electrode according to claim 8 , wherein the kneading step in the first step is performed by further adding a conductive assistant.
11. The method for producing a negative electrode according to claim 8 , wherein the carbon-based active material particles include graphite particles.
12. The method for producing a negative electrode according to claim 8 , wherein the metal-based active material particles contain one or more types of particles selected from the group consisting of Si, SiO x , and a composite of Si and C.
13. A method for producing a non-aqueous electrolyte secondary battery, comprising the step of producing a negative electrode by the method for producing a negative electrode according to any one of claims 8 to 12.
Citation Information
Patent Citations
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2013229163A
Production method of slurry for forming active material layer
JP2014137881A
Secondary cell
JP2019145276A
Negative electrode
JP2020087777A
Manufacturing method of negative electrode for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2022072942A